Identification of vanadium dopant sites in the metal–organic framework DUT-5(Al). Issue 12 (19th March 2021) - Maes, Kwinten; Martin, Lisa I. D. J.; Khelifi, Samira; Hoffman, Alexander; Leus, Karen; Van Der Voort, Pascal; Goovaerts, Etienne; Smet, Philippe F.; Van Speybroeck, Veronique; Callens, Freddy; Vrielinck, Henk
Abstract : EPR spectra of V-doped DUT-5(Al) reveal four types of paramagnetic dopant species. Spin-Hamiltonian analysis and spectrum decomposition as function of V-content are supplemented with structural information from other spectroscopic techniques. Abstract : Studying the structural environment of the V IV ions doped in the metal–organic framework (MOF) DUT-5(Al) ((Al III OH)BPDC) with electron paramagnetic resonance (EPR) reveals four different vanadium-related spectral components. The spin-Hamiltonian parameters are derived by analysis of X-, Q- and W-band powder EPR spectra. Complementary Q-band Electron Nuclear DOuble Resonance (ENDOR) experiments, Scanning Electron Microscopy (SEM), Energy Dispersive X-ray spectroscopy (EDX), X-Ray Diffraction (XRD) and Fourier Transform InfraRed (FTIR) measurements are performed to investigate the origin of these spectral components. Two spectral components with well resolved 51 V hyperfine structure are visible, one corresponding to V IV O substitution in a large (or open) pore and one to a narrow (or closed) pore variant of this MOF. Furthermore, a broad structureless Lorentzian line assigned to interacting vanadyl centers in each other's close neighborhood grows with increasing V-concentration. The last spectral component is best visible at low V-concentrations. We tentatively attribute it to (V IV O) 2+ linked with DMF or dimethylamine in the pores of the MOF. Simulations using these four spectral components convincingly reproduce the experimental spectra and allow to estimate the contribution of each vanadyl species as a function of V-concentration.